Knowledge to ecological preferences in a tropical epiphytic algae to use with eutrophication indicators (2013)
ABSTRACT: In Ayapel floodplain periphyton associated to macrophyte roots on the basis of material was collected in fourteen samp- ling sites in nine moments of compilation. From the analysis of the samples were recorded 550 algal species, of which 56% were diatoms. Furthermore it was valued relative abundances of taxa and the average physicochemical variables to identify the optimal values and tolerance ranges of species. In the case of nitrates optimal value was below 2 mg/L for all algae except for Actinella sp. and Euastrum sinuosum which optimal values were close to zero with low variability. Regarding all species the algal nitrite concentration showed optimum values below 2 mg/L except Encyonema minutum and E. sinuosum whose optimum were 0.4 and 0.5 mg/L respectively. About nitrogen as ammonia was repeated the above situation, i.e. optimum values below 2 mg/L except for E. minutum and E. sinuosum. Respect to phosphorus the species with optimum greater than 0.6 mg/L are the diatoms, in contrast, the lowest values were optimal for E. sinuosum and Actinella sp. From the viewpoint of bioindication high abundance of Synedra goulardii indicates high transparency, Ulnaria ulna and Planothidium lanceolatum indicate lower concentration of dissolved oxygen and water temperature between 29°C - 30°C, Actinella aff. robusta, E. minutum, Cylindrospermopsis raciborski, Lyngbya cf. limnetica, Euno-tia naegueli, Navicula cryptocephala, Diadesmis confervaceae, Frustulia rhomboides and Aulacoseira granulata. Indi-cating low electrical conductivity (<100 μS/cm), Synedra goulardii indicating neutral waters, Actinella eunotioides and Euastrum sinuosum indicate low nitrate concentration (<0.2 mg/L), Eunotia minor indicating midrange nitrite concen-tration (0.2 - 0.5 mg/L), Ulnaria ulna, Planothidium lanceolatum indicating low ammoniacal nitrogen concentration (<0.2 mg/L) and Actinella eunotioides indicating low soluble reactive phosphorus concentration (<0.2 mg/L).